Impacts of Temperature, CO2, and Salinity on Phytoplankton Community Composition in the Western Arctic Ocean - Sugie, Koji; Fujiwara, Amane; Nishino, Shigeto; Kameyama, Sohiko; Harada, Naomi (Frontiers in Marine Science, 2020)
The Arctic Ocean has been experiencing rapid warming, which accelerates sea ice melt. Further, the increasing area and duration of sea ice-free conditions enhance ocean uptake of CO2. We conducted two shipboard experiments in September 2015 and 2016 to examine the effects of temperature, CO2, and salinity on phytoplankton dynamics to better understand the impacts of rapid environmental changes on the Arctic ecosystem. Two temperature conditions (control: <3°C and 5°C above the control), two CO2 levels (control: ~300 μatm and 300/450 μatm above the control; i.e., 600/750 μatm), and two salinity conditions (control: 29 in 2015 and 27 in 2016, and 1.4 below the control) conditions were fully factorially manipulated in eight treatments. Higher temperatures enhanced almost all phytoplankton traits in both experiments in terms of chl-a, accessory pigments and diatom biomass. The diatom diversity index decreased due to the replacement of chain-forming Thalassiosira spp. by solitary Cylindrotheca closterium or Pseudo-nitzschia spp. under higher temperature and lower salinity in combination. Higher CO2 levels significantly increased the growth of small-sized phytoplankton (<10 μm) in both years. Decreased salinity had marginal effects but significantly increased the growth of small-sized phytoplankton under higher CO2 levels in terms of chl-a in 2015. Our results suggest that the smaller phytoplankton tend to dominate in the shelf edge region of the Chukchi Sea in the western Arctic Ocean under multiple environmental perturbations.